2007
DOI: 10.1038/sj.bjc.6603724
|View full text |Cite
|
Sign up to set email alerts
|

WTH3 is a direct target of the p53 protein

Abstract: Previous results showed that overexpression of the WTH3 gene in multidrug resistance (MDR) cells reduced MDR1 gene expression and converted their resistance to sensitivity to various anticancer drugs. The WTH3 gene promoter was found to be differentially regulated in paired MDR vs non-MDR MCF7 cells owing to epigenetic modifications and transcription factor modulations. To understand further the mechanisms that govern WTH3's differential expression, we uncovered a p53-binding site in its promoter, which indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 42 publications
1
19
0
3
Order By: Relevance
“…The similar results obtained in our study suggest that the underlying mechanism might be conserved among vertebrates. MES-SA cells are reported to possess a wild type p53 [31] which is activated upon sensing DNA damage and consequently upregulates the cyclin dependent kinase inhibitor (CKI) p21 inducing a G1 arrest [32]. This scenario was confirmed in western blot results shown in Figure 4E.…”
Section: Resultssupporting
confidence: 68%
“…The similar results obtained in our study suggest that the underlying mechanism might be conserved among vertebrates. MES-SA cells are reported to possess a wild type p53 [31] which is activated upon sensing DNA damage and consequently upregulates the cyclin dependent kinase inhibitor (CKI) p21 inducing a G1 arrest [32]. This scenario was confirmed in western blot results shown in Figure 4E.…”
Section: Resultssupporting
confidence: 68%
“…23 a breast tumor cell line that is intrinsically radioresistant. 23,24 The clonogenic survival data presented in Figure 7A confirm that Hs578t cells were significantly less radiosensitive than MCF-7 cells. Figure 7B further confirmed the findings of Mineva et al 23 that 1,25D 3 enhances radiation sensitivity.…”
Section: Do Not Distributementioning
confidence: 53%
“…[18][19][20][21] Our current studies were designed to evaluate the involvement of autophagy in radiosensitization by EB1089 as well as extending the work to the hormonally active and natural form of 1,25D 3 . In addition, studies were performed in breast tumor cells that are intrinsically resistant to radiation and chemotherapy through overexpression of Her-2/neu (MCF7/Her-2/neu cells), 22 in Hs578t cells, another (moderate Her-2/neu overexpression, p53 mutant) breast tumor cell line that was shown to be radiosensitized by 1,25D 3 , 23,24 as well as p53 mutant, Her-2 overexpressing BT474 cells, a breast tumor cell line that has been reported to express the vitamin D receptor. 25 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, WTH3 does not undergo modification following translation and is unable to bind to the membrane to exert a biological function (18)(19)(20). Since WTH3 was identified during the study of tumor drug resistance, a number of studies have investigated the methylation and transcriptional regulation of the gene (5,21). In the present study, the expression level of WTH3 in human breast cancer tissue and breast cancer cell lines was investigated and an abnormal expression was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Using the previously constructed cell lines, the results of the present study indicated that WTH3 was able to inhibit certain biological behaviors of the breast cancer cells, including cell proliferation, migration and invasion. WTH3 may inhibit cell proliferation through the activation of one or more tumor suppressor genes, including the P53 transcription factor, or negative regulation of the WT transcription factor and DNA repair factors BRCA1 and BRCA2, all of which can be effective in promoting apoptosis and the inhibition of tumor cell growth (21,22). However, the exact mechanism underlying the effects of WTH3 requires further study.…”
Section: Discussionmentioning
confidence: 99%